2022
DOI: 10.1108/crr-10-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental scanning on organizational resilience and competitive advantage: a study of Egyptian SMEs

Abstract: PurposeThis paper aims to examine the impact of environmental scanning (ES) on competitive advantage (CA) through the mediation of organizational resilience dimensions within manufacturing small and medium-sized enterprises (SMEs) in Egypt.Design/methodology/approachThis study adopts a cross-sectional design to collect data. This study used a self-administered questionnaire to collect data from a sample of 249 Egyptian SMEs. This study employed the Smart partial least square structural equation modeling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 112 publications
1
2
0
Order By: Relevance
“…Moreover, Vakilzadeh and Haase (2021) asserted that environmental scanning, as a predictive tool, is considered a building block of resilience. Besides, in accordance with our results, YahiaMarzouk and Jin (2022a) found that environmental scanning activities positively affected OR, namely robustness and agility.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, Vakilzadeh and Haase (2021) asserted that environmental scanning, as a predictive tool, is considered a building block of resilience. Besides, in accordance with our results, YahiaMarzouk and Jin (2022a) found that environmental scanning activities positively affected OR, namely robustness and agility.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…An important contribution of our study pertains to the impact of relational capital on environmental scanning. Despite the large number of empirical research that have investigated ES activities in firms around the world (e.g., Jorosi, 2008 ; Wong and Hung, 2012 ; Aldehayyat, 2015 ), and the empirical studies that confirmed its positive impact on resilience and survival during crises (e. g., Vakilzadeh and Haase, 2021 ; YahiaMarzouk and Jin, 2022a , b ), studies examining the factors that may facilitate the environmental scanning activities are still largely lacking. In this regard, we argued that RC enables enterprises to collaborate with other businesses, communities, and governmental agencies out of a sense of mutual respect and trust in order to gather important information.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategic management accounting is a dataset that executives use as an effective tool that helps executives in strategic planning, decision-making, and operations contributes to greater business efficiency (Navarro-Garcí a et al, 2016;Wajdi and Arsjah, 2019). Additionally, strategic management accounting reflects information used to develop business strategies to create competitive advantages over competitors (Kaneko and Yimruan, 2017), even during changing business situations (Panjaitan et al, 2018;YahiaMarzouk and Jin, 2022). Consequently, the implementation of strategic management accounting integrated with technological information and market data with future visions enables executives to evaluate opportunities and risks in business competition, allowing them to formulate appropriate strategies based on their resource capabilities (Stocker et al, 2021).…”
Section: Strategic Management Accounting (Sma)mentioning
confidence: 99%